Answer:
The expression can be written as:
5(2) + 6(3) + 2(4).
if I'm wrong, please tell me
move variable to the left side and change its sign
-3x+8=6y
Move constant to the right side and change its sign
-3x=6y-8
Divide both sides of the equation by -3
x=-2y+8/3
Answer:
the 3rd one from top
Step-by-step explanation:
because the coefficient is largest
Answer:
The correct answer is option A. Base = 11 cm and height = 13 cm
Step-by-step explanation:
It is given that, height of a triangle is 2 cm more than its base.Then height is increased by 2 cm.Then the area of triangle becomes 82.5 cm²
<u>To find the base an d height of original triangle</u>
Let x be the original base 'b' then the height h = x + 2
New height h = x + 2 + 2 = x + 4
Area = bh/2
82.5= (x(x + 4)/2
165 = x² + 4x
x + 4x - 165 = 0
Solving we get x = 11 and x = -15
Take positive value x = 11
Therefore base = 11 and height = x + 2 = 13 cm
The correct answer is option A. Base = 11 cm and height = 13 cm